A Systems Pedagogy and a Novel Brainstorming Approach to Initiate Pico/Nano/Micro-Satellite (PNMSat) Engineering Research and Development at Academic Institutions in India - Asundi, Sharanabasaweshwara; Rao, Divya (Journal of Engineering Education Transformations, 2018)
The article describes the outcome of an initiative to educate the youth in India, motivate them to seek diverse careers, fulfilling livelihoods and contribute towards the nation by engaging them in pico/nano/micro-satellite (PNMSat) design engineering. A systems pedagogy, derived out of a systems engineering approach developed for the design and development of PNMSat/CubeSat missions, is used to teach a comprehensive course in PNMSat design engineering. A novel approach used in the course involves brainstorming the participants to conceive a PNMSat payload and teach the PNMSat bus design to accommodate the conceived payload. This approach and the comprehensive treatment of a course in satellite design are the first of their kind in India; particularly in the field of small satellite design engineering. The article describes in detail the course contents, the novel approach and the results of the course assessments from three offerings â€“ Summer 2015, Summer 2016 and Summer 2017. The article presents the results of surveys conducted to assess the impact on the participants’ awareness in PNMSat engineering, motivation to pursue diverse careers and fulfilling livelihoods. It’s been observed that engineering institutions in India are keen to initiate a PNMSat program but have struggled to do so due to the lack of a systematic approach. The article provides an insight into addressing this problem and initiating a PNMSat program at engineering institutions in India.